The Debate Between Realism and Formalism in Contemporary International Law (Emphasizing the Procedure of the International Court of Justice) - Sepanta Mojtahedzadeh (پژوهشهای حقوقی)
Legal realism and legal formalism as two methods of judicial decision-making in national and international courts have been hot theoretical and philosophical topics among writers, judges, and lawyers in recent decades. Both methods have supporters and each has presented arguments to strengthen their views. In this research, with a descriptive-analytical method and using the library method and using reliable internet sources to collect data, an attempt has been made to answer the question that contemporary international law is at the crossroads between realism and legal formalism Which way is it going and what method does the International Court of Justice, follow in issuing its opinions? The answer that we got in brief is that the debate between these two methods in contemporary international law and as a result in the opinions of the International Court of Justice, has not had a clearly defined winner. However, the tendency is more towards formalism.